1998
DOI: 10.1038/sj.pcan.4500228
|View full text |Cite|
|
Sign up to set email alerts
|

Transitions in health-related quality of life during the first nine months after diagnosis with prostate cancer

Abstract: Health-Related Quality of Life (HRQOL) is an important outcome measure in the study of prostate cancer. There are few data regarding the effect of sociodemographic variables, such as insurance status, educational level, marital status or income, on HRQOL. We examined whether these or other sociodemographic and clinical variables are predictive of HRQOL outcomes using an observational database of prostate cancer patients accrued from a wide array of clinical practice settings.We studied 131 patients with newly-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…They also found that men with higher education levels were less likely to have a return to baseline HRQOL. Penson et al [33] noted similar findings with regard to marital status. In addition, they found a relationship between income, insurance status, and certain HRQOL domains.…”
Section: Quality Of Life Following Radical Prostatectomysupporting
confidence: 64%
“…They also found that men with higher education levels were less likely to have a return to baseline HRQOL. Penson et al [33] noted similar findings with regard to marital status. In addition, they found a relationship between income, insurance status, and certain HRQOL domains.…”
Section: Quality Of Life Following Radical Prostatectomysupporting
confidence: 64%
“…Partner characteristics might be considered a psychological factor. Prior reports from the Prostate Cancer Outcomes Study [33] and the CaPSURE data set [34] documented independent associations between sexuality and race/ethnicity and insurance status. Moreover, the age difference between patients and partners was a significant predictive factor of maintaining postoperative potency independent of the patient's age [35].…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer survival is clearly higher for married men [69] and, in the US, for men of higher SEP, but no association between survival and SEP was found in Canada [70]. Lower SEP is also associated with lower quality of life, both at diagnosis and following treatment [71], while being married is associated with a higher quality of life [72]. Prostate cancer mortality is also associated with lower family position [73].…”
Section: Socioeconomic Position (Sep)mentioning
confidence: 97%